A Critical Assessment of Seven Reports on Financial Reform: A Minskyan Perspective. Part II: Treasury, CRMPG reports, Financial Stability Forum - Eric Tymoigne (Levy Economics Institute of Bard College, 2009)
This four-part study is a critical analysis of several reports dealing with the reform of the financial system in the United States. The study uses Minsky's framework of analysis and focuses on the implications of Ponzi finance for regulatory and supervisory policies. The main conclusion of the study is that, while all reports make some valuable suggestions, they fail to deal with the socioeconomic dynamics that emerge during long periods of economic stability. As a consequence, it is highly doubtful that the principal suggestions contained in the reports will provide any applicable means to limit the worsening of financial fragility over periods of economic stability. The study also concludes that any meaningful systemic and prudential regulatory changes should focus on the analysis of expected and actual cash flows (sources and stability) rather than capital equity, and on preventing the emergence of Ponzi processes. The latter tend to emerge over long periods of economic stability and are not necessarily engineered by crooks. On the contrary, the pursuit of economic growth may involve the extensive use of Ponzi financial processes in legal economic activities. The study argues that some Ponzi processes - more precisely, pyramid Ponzi processes - should not be allowed to proceed, no matter how severe the immediate impact on economic growth, standards of living, or competitiveness. This is so because pyramid Ponzi processes always collapse, regardless how efficient financial markets are, how well informed and well behaved individuals are, or whether there is a 'bubble' or not. The longer the process is allowed to proceed, the more destructive it becomes. Pyramid Ponzi processes cannot be risk-managed or buffered against; if economic growth is to be based on a solid financial foundation, these processes cannot be allowed to continue. Finally, a supervisory and regulatory process focused on detecting Ponzi processes would be much more flexible and adaptive, since it would not be preoccupied with either functional or product limits, or with arbitrary ratios of 'prudence'. Rather, it would oversee all financial institutions and all products, no matter how new or marginal they might be. - See also, Working Paper Nos. 574.1, 574.3, and 574.4.
Keywords: E58; G01; G18; G28; G38; 330; regulation; supervision; financial reform; Minsky; central banking